Mutational analysis and clinical correlation of metastatic colorectal cancer. Issue 10 (5th February 2014) - Russo, Andrea L.; Borger, Darrell R.; Szymonifka, Jackie; Ryan, David P.; Wo, Jennifer Y.; Blaszkowsky, Lawrence S.; Kwak, Eunice L.; Allen, Jill N.; Wadlow, Raymond C.; Zhu, Andrew X.; Murphy, Janet E.; Faris, Jason E.; et al.
<x xml:space="preserve">Abstract</x> BACKGROUND Early identification of mutations may guide patients with metastatic colorectal cancer toward targeted therapies that may be life prolonging. The authors assessed tumor genotype correlations with clinical characteristics to determine whether mutational profiling can account for clinical similarities, differences, and outcomes. METHODS Under Institutional Review Board approval, 222 patients with metastatic colon adenocarcinoma (n = 158) and rectal adenocarcinoma (n = 64) who underwent clinical tumor genotyping were reviewed. Multiplexed tumor genotyping screened for >150 mutations across 15 commonly mutated cancer genes. The chi‐square test was used to assess genotype frequency by tumor site and additional clinical characteristics. Cox multivariate analysis was used to assess the impact of genotype on overall survival. RESULTS Broad‐based tumor genotyping revealed clinical and anatomic differences that could be linked to gene mutations. NRAS mutations were associated with rectal cancer versus colon cancer (12.5% vs 0.6%; P < .001) and with age ≥56 years (7% vs 0.9%; P = .02). Conversely, v‐raf murine sarcoma viral oncogene homolog B (BRAF) mutations were associated with colon cancer (13% vs 3%; P = .024) and older age (15.8% vs 4.6%; P = .006). TP53 mutations were associated with rectal cancer (30% vs 18%; P = .048), younger age (14% vs 28.7%; P = .007), and men (26.4% vs 14%; P = .03). Lung metastases were associated with PIK3CA mutations (23% vs 8.7%; P = .004). Only mutations in BRAF were independently associated with decreased overall survival (hazard ratio, 2.4; 95% confidence interval, 1.09‐5.27; P = .029). CONCLUSIONS The current study suggests that underlying molecular profiles can differ between colon and rectal cancers. Further investigation is warranted to assess whether the differences identified are important in determining the optimal treatment course for these patients. Cancer 2014;120:1482–1490. © 2014 American Cancer Society.